Reconstruction of Coherent Pairs of Synthetic Aperture Radar Data Acquired in Interrupted Mode - Pinheiro, Muriel; Rodriguez-Cassola, Marc; Prats-Iraola, Pau; Reigber, Andreas; Krieger, Gerhard; Moreira, Alberto (IEEE Transactions on Geoscience and Remote Sensing, 2015)
A number of synthetic aperture radar (SAR) systems might work in interrupted operation for different purposes. Examples are cooperative bistatic SAR systems with a synchronization link between the transmitter and receiver or multistatic systems operating in receive-only mode, among others. As a direct consequence, the acquired raw data contain missing echoes presented in a periodical or random pattern. Since the missing raw data introduce artifacts in the processed images, recovery methods have to be applied. Usually, spectral-estimation-based interpolators can be used to recover data. Although such algorithms show good performance for pointlike targets, their efficiency is decreased for distributed scatterers. In this paper, we propose, for a coherent pair of SAR images, the use of the common information in one image to reconstruct the other and vice versa. The conditions required for the proper use of the approach are discussed, and the method is verified using simulated data. One special case of study is the TanDEM-X mission, where the cooperative nature of the bistatic operation requires the periodic exchange of information between the satellites in order to gather information for calibration and synchronization, creating a periodic missing data pattern in the raw data. For this case of study, the reconstruction methods based on spectral estimation are analyzed, and the proposed reconstruction using cross-information is validated.
DLR Import::2019-04-02
Keywords: Bistatic synthetic aperture radar (SAR); cross-reconstruction; reconstruction of missing data; SAR; SAR interferometry; spectral estimators